Stability Analysis for Grain Yield and its Components in Soybean (Glycine max L. Merrill) - Jakhar, Ranjeet Singh; Salke, P. S.; Misal, A. M.; Sonawane, V. G.; Srikanth, K.; Borade, S. R.; Rajveer (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was conducted with twenty two genotypes including five checks of soybean (Glycine max L.) for stability performance over three environments in a R.B.D. with three replication during kharif-2016. The analysis of variance revealed significant differences among the genotypes for all traits studied over all environments, indicating sufficient amount of variability present. G X E interaction is highly significant for all character studied except plant height, number of pods per plant and oil content. Environment (linear) was highly significant for all traits except number of seeds per pod and oil content. The predominance of linear component would help in predicting the performance of genotypes across environment. Considering the nature of stability, two genotypes MAUS-740, MAUS-710 were found promising and they had stable performance over three environments for grain yield per plant-1 while MAUS-614 was suitable for favorable environment. For number of branches plant-1 two genotypes, KDS-980 and MACS-1460 showed superiority for average response and stability under all environments. For number of pod per plant three genotypes, KDS-1045, AMS-100-39-1 and MAUS-706 had stable performance in all three environments. For number of seeds pod-1 genotypes, AMS-1002, AMS-1003, MAUS-706 and MAUS-158 suitable under unfavorable environment.The genotypes, MAUS-740, MAUS-614 had stable performance over three environments for 100 seed weight. Use of genotype with wide (MAUS-740, MAUS-710) or specific stability (KDS-921, MACS-1543, AMS-MB-5-19, KDS-1045, AMS-100-39-1, MACS-1460, JS-93-05, MAUS-706)) in development of new varieties with desired nature of adaptability suggested.